2020
DOI: 10.4103/ijt.ijt_123_19
|View full text |Cite
|
Sign up to set email alerts
|

A study of association of premature graying of hair and osteopenia in North Indian population

Abstract: Context: Hair graying is one of the signs of human aging and is caused by a progressive loss of pigmentation from growing hair shafts. Studies have shown a correlation of early hair graying with osteopenia, indicating that premature graying could serve as an early marker of osteopenia. Aim: To compare the degree of osteopenia in individuals with premature graying of hair (PGH) compared to ordinary individuals. Settings and Design: We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…However, Morton et al in the Rancho Bernardo study, and subsequently Agarwal et al, found no significant association between PHG and bone mineral density. [18][19][20]…”
Section: Osteopeniamentioning
confidence: 99%
“…However, Morton et al in the Rancho Bernardo study, and subsequently Agarwal et al, found no significant association between PHG and bone mineral density. [18][19][20]…”
Section: Osteopeniamentioning
confidence: 99%
“…I refer to the interesting case–control study published by Agarwal et al . [ 1 ] in March–April 2020 issue of the International Journal of Trichology . On using ultrasound bone densitometer to estimate bone mineral density (BMD), the authors compared the grade of osteopenia in individuals with premature graying of hair (PGH) and those without PGH.…”
mentioning
confidence: 99%
“…They found that the mean BMD in the case group was 0.76 ± 1.00 compared to 0.68 ± 1.11 in the control group with no statistically significant difference ( P = 0.649). [ 1 ] They concluded that was no significant correlation between PGH and steopenia. [ 1 ] I presume that due to the following methodological limitation, the study results ought to be cautiously interpreted.…”
mentioning
confidence: 99%
See 2 more Smart Citations